PIMS: A Reexamination - Anderson, Carl R.; Paine, Frank T. (Academy of Management Review, 1978)
The PIMS research program is examined in eight key areas. In general, the PIMS approach was found to be the best current attempt to gather and analyze data on strategic actions of businesses. Suggested improvements will enhance its usefulness to the practitioner. These improvements will further the state of theoretical model building and validation in the strategy field.